The Influence of Working Capital on Remaining Business Results at the CU Bahtera Sejahtera Savings and Loan Cooperative - Grasiana Imu Setu; Andreas Rengga; Cicilia Ayu Wulandari Nuwa (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine the effect of Working Capital on Remaining Business Results . The data for this research is data in the form of financial reports from 2016 - 2021 obtained from the CU Bahtera Sejahtera Savings and Loans Cooperative. The research method used is a quantitative descriptive method. The data collection techniques used were interviews and documentation while the analysis used was the Normality Test, Simple Linear Regression analysis, Hypothesis Testing (t test) and analysis of the coefficient of determination. The tool used is SPSS V.20 For Windows. The statistical results of the t test show that the working capital variable has no effect on the remaining business results variable. Thus, the results of this research reject that Working Capital has an influence on the Remaining Business Results of the CU Bhatera Sejahtera Savings and Loans Cooperative. The working capital owned by the cooperative is quite large, but the amount of working capital is not necessarily able to increase the remaining business results. 1.2%. This shows that the remaining business results can be explained by working capital of 1.2%, while the remaining 98.8% is influenced by other factors not analyzed in this research.